THE EFFECT OF THE IMPLEMENTATION OF THE 2013 CURRICULUM ON THE ARABIC LEARNING OUTCOMES OF GRADE 10 STUDENTS AT MAN 1 BOJONEGORO - Nurdiana, Ryan; Muamaroh, Dzun Nur Nafiah; Abidin, Munirul (CV. Amerta Media, 2023)
This study was to test whether there was an effect of curriculum application 2013 on the Arabic learning outcomes of grade 10 students of MAN 1 Bojonegoro. Sempel collection using simple random sampling. The sample taken was as many as 20 respondents of grade 10 students. This study uses 1 independent variable, namely the application of curriculum (x) and 1 dependent variable, namely learning outcomes (y). The data used in this study are primary data in the form of questionnaires and secondary data in the form of books, journals related to this study. This study used quantitative. The data analysis technique used in this study is simple linear regression analysis. The result of this study is significant by 0.04 meaning <0.05. In addition to the coefficient of determination, a value of 25.9% is obtained so that it can be concluded that variable X has an effect of 0.259 or 25.9 on variable Y. Keywords: Influence, Curriculum, Arabic Learning